2016
DOI: 10.1016/j.msea.2016.09.091
|View full text |Cite
|
Sign up to set email alerts
|

On the role of initial void geometry in plastic deformation of metallic thin films: A molecular dynamics study

Abstract: Void growth is usually considered one of the most critical phases leading to dynamic fracture of ductile materials. Investigating the detailed process of void growth at the nanoscale aids in understanding the damage mechanism of metals. While most atomistic simulations by far assume circular or spherical

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 39 publications
4
20
0
Order By: Relevance
“…Overall, a majority of defects nucleate at the top/bottom sides of the void, which is a reflection of the fact that these two sites have the highest stress concentrations in a model subject to a tensile loading along the y direction. We remark that the plastic deformation zone in α-Fe (exhibited by nucleation and evolution of slip bands, full dislocations, and twins) is much more complicated than that in FCC Cu, in which the dislocation nucleation dominates the plasticity [16]. As a result, the development of dislocation density with an increasing strain would not be a good indicator of defect evolution in this work.…”
Section: Defect Nucleation and Evolutionmentioning
confidence: 83%
See 1 more Smart Citation
“…Overall, a majority of defects nucleate at the top/bottom sides of the void, which is a reflection of the fact that these two sites have the highest stress concentrations in a model subject to a tensile loading along the y direction. We remark that the plastic deformation zone in α-Fe (exhibited by nucleation and evolution of slip bands, full dislocations, and twins) is much more complicated than that in FCC Cu, in which the dislocation nucleation dominates the plasticity [16]. As a result, the development of dislocation density with an increasing strain would not be a good indicator of defect evolution in this work.…”
Section: Defect Nucleation and Evolutionmentioning
confidence: 83%
“…Tang et al [27] similarly reported such a slip-to-twinning transition as the strain rate increases, in a voided BCC Ta model subject to a uniaxial tensile strain or a hydrostatic tensile loading; their MD simulations also revealed a special type of dislocation shear loop at the void surface that can expand as partial or perfect dislocations, evolving into prismatic loops through reaction with each other or developing into twins [28]. However, the atomic-scale mechanisms of the effects of the initial void geometry in nanovoid growth, which have recently been explored in FCC metals [16,19,29], remain largely unknown in BCC metals.…”
Section: Introductionmentioning
confidence: 99%
“…Prior atomistic studies revealed that the nanovoid growth process is affected by many factors, including, but not limited to, strain rate [9], temperature [10], initial porosity [11], initial void shape [12], and crystallographic orientations [13,14,15]. Compared with face-centered cubic (FCC) [1,10,12] and body-centered cubic (BCC) [9,2,11] systems, there exist much fewer studies of nanvoids in metals with a hexagonal close-packed (HCP) lattice, in part due to a lack of reliable interatomic potential and more complicated slip/twinning systems in the latter.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with face-centered cubic (FCC) [1,10,12] and body-centered cubic (BCC) [9,2,11] systems, there exist much fewer studies of nanvoids in metals with a hexagonal close-packed (HCP) lattice, in part due to a lack of reliable interatomic potential and more complicated slip/twinning systems in the latter. Particularly for HCP Mg, the lightest and the third most abundant element in the Earth's crust among all metals, most atomistic simulations in the literature concerned nanocracks [16,17,18,19]; to the best of our knowledge, only a few MD and atomistic-based multiscale studies have been devoted to nanovoids [20,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, nanotwinned small‐sized metallic systems, for example, nanopillars and nanotubes, with either parallel or fivefold CTBs, remain relatively lightly explored . Compared with 3D nanocrystals, 1D nanopillars/nanotubes with free surfaces attain additional geometric features including outer/inner diameter and cross‐sectional shape which, along with the CTB spacing, may significantly alter their mechanical properties . On the other hand, deformation may annihilate nanotwins and increase the CTB spacing .…”
mentioning
confidence: 99%